PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN CABANG LANGSA - Surya Darma (Universitas Islam Sumatera Utara, 2020)
In an increasingly complex and ever-changing business environment, the study of leadership can no longer be as simple as using these two dimensions. Likewise, efforts to find the best leadership style that applies throughout time will be in vain. There is a need to find a leadership model that is more relevant to complex situations like today. Transformational leadership is one of the